Pharmacological inhibition of the chemokine CCL2 (MCP-1) diminishes liver macrophage infiltration and steatohepatitis in chronic hepatic injury. Issue 3 (3rd August 2011) - Baeck, Christer; Wehr, Alexander; Karlmark, Karlin Raja; Heymann, Felix; Vucur, Mihael; Gassler, Nikolaus; Huss, Sebastian; Klussmann, Sven; Eulberg, Dirk; Luedde, Tom; Trautwein, Christian; Tacke, Frank
Abstract : Objective: Monocyte chemoattractant protein-1 (MCP-1, CCL2), the primary ligand for chemokine receptor C–C chemokine receptor 2 (CCR2), is increased in livers of patients with non-alcoholic steatohepatitis (NASH) and murine models of steatohepatitis and fibrosis. It was recently shown that monocyte/macrophage infiltration into the liver upon injury is critically regulated by the CCL2/CCR2 axis and is functionally important for perpetuating hepatic inflammation and fibrogenesis. The structured L-enantiomeric RNA oligonucleotide mNOX-E36 (a so-called Spiegelmer) potently binds and inhibits murine MCP-1. Pharmacological inhibition of MCP-1 with mNOX-E36 was investigated in two murine models of chronic liver diseases. Methods: Pharmacological inhibition of MCP-1 by thrice-weekly mNOX-E36 subcutaneously was tested in murine models of acute or chronic carbon tetrachloride (CCl4 )- and methionine–choline-deficient (MCD) diet-induced chronic hepatic injury in vivo. Results: Antagonising MCP-1 by mNOX-E36 efficiently inhibited murine monocyte chemotaxis in vitro as well as migration of Gr1 + (Ly6C + ) blood monocytes into the liver upon acute toxic injury in vivo. In murine models of CCl4 - and MCD diet-induced hepatic injury, the infiltration of macrophages into the liver was significantly decreased in anti-MCP-1-treated mice as found by fluorescence-activated cell sorting (FACS) analysis and immunohistochemistry. In line with lower levels of intrahepatic macrophages, proinflammatory cytokines (tumour necrosis factor α, interferon γ and interleukin 6) were significantly reduced in liver tissue. Overall fibrosis progression over 6 (CCl4 ) or 8 weeks (MCD diet) was not significantly altered by anti-MCP-1 treatment. However, upon MCD diet challenge a lower level of fatty liver degeneration (histology score, Oil red O staining, hepatic triglyceride content, lipogenesis genes) was detected in mNOX-E36-treated animals. mNOX-E36 also ameliorated hepatic steatosis upon therapeutic administration. Conclusions: These results demonstrate the successful pharmacological inhibition of hepatic monocyte/macrophage infiltration by blocking MCP-1 during chronic liver damage in two in vivo models. The associated ameliorated steatosis development suggests that inhibition of MCP-1 is an interesting novel approach for pharmacological treatment in liver inflammation and steatohepatitis.